2020
DOI: 10.3390/ijms21228635
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Fibroblasts and Immune Cells Following DNA Damage Induced by Ionizing Radiation

Abstract: Cancer-associated fibroblasts (CAF) form the basis of tumor microenvironment and possess immunomodulatory functions by interacting with other cells surrounding tumor, including T lymphocytes, macrophages, dendritic cells and natural killer cells. Ionizing radiation is a broadly-used method in radiotherapy to target tumors. In mammalian cells, ionizing radiation induces various types of DNA damages and DNA damage response. Being unspecific, radiotherapy affects all the cells in tumor microenvironment, including… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 82 publications
1
28
0
Order By: Relevance
“…It was previously shown that the expression and activity of DNA-PKcs are increased in the NSPC murine cells when compared to mouse embryonic fibroblasts [26], suggesting that DNA-PKcs can be essential for homeostasis of NSPCs. Expression and activity of NHEJ vary in different cell types and require closer attention in future research [33]. Our data further highlighted this observation, and our findings suggest that the DNA-PKcs is required for NSPC proliferation and self-renewal capacities, although its role is partially compensated by XLF (Figure 2B,C).…”
Section: Discussionsupporting
confidence: 79%
“…It was previously shown that the expression and activity of DNA-PKcs are increased in the NSPC murine cells when compared to mouse embryonic fibroblasts [26], suggesting that DNA-PKcs can be essential for homeostasis of NSPCs. Expression and activity of NHEJ vary in different cell types and require closer attention in future research [33]. Our data further highlighted this observation, and our findings suggest that the DNA-PKcs is required for NSPC proliferation and self-renewal capacities, although its role is partially compensated by XLF (Figure 2B,C).…”
Section: Discussionsupporting
confidence: 79%
“…CAFs are inherently resistant to the clastogenic effects of radiotherapy. Radiation fails to cause persistent DNA damage in CAF, and CAFs resist apoptosis following clinically applied doses of radiotherapy [77,78]. In fact, radiation and MAPK inhibition (U0126) have been reported to cause no dose-limiting effect on CAF [79].…”
Section: Cafs and Resistance To Radiotherapiesmentioning
confidence: 99%
“…The other reason for this differential survival phenomenon is that CAFs exhibit senescence following radiation. Xenograft studies demonstrated that highly plastic CAFs recover from the radiation subsequently, via: (1) autocrine/paracrine secretion of cytokines and growth factors [80], (2) producing a distinct combination of immunoregulatory molecules [78] post senescence, and (3) increasing ability to repair DNA damage and altered indices of oxidative metabolism as demonstrated by increases in protein carbonylation, mitochondrial superoxide anion levels, and modulation of the activity of the antioxidants, manganese superoxide dismutase and catalase. [81].…”
Section: Cafs and Resistance To Radiotherapiesmentioning
confidence: 99%
“…DNA in our cells is constantly modified by internal and external factors. For example, metabolic byproducts, ionizing radiation (IR), ultraviolet (UV) light, and medicines can induce spontaneous DNA lesions [ 1 , 2 , 3 ]. However, DNA modifications can also be programmed.…”
mentioning
confidence: 99%
“…Another aspect of this Special Issue is the various anti-cancer therapies and their combinations. These therapies, such as IR and cisplatin, induce extensive DNA damage in rapidly growing cells [ 3 ]. These DNA damages, if unresolved over time, can induce DDR and cell cycle checkpoint arrest, which leads to p53-mediated Bcl-xL-controlled apoptosis [ 13 ].…”
mentioning
confidence: 99%